Integrating Clinical Nutrition Into Internal Medicine Practice To Combat Chronic Disease For Comprehensive Patient Care (The Review of Diabetic Studies, 2025)
Background: Non-communicable diseases (NCDs) predominantly cardiovascular disease, type 2 diabetes mellitus (T2DM), and malignance account for over 70% of global mortality. While suboptimal dietary habits represent a primary modifiable risk factor, nutrition remains and under addressed pillar within internal medicine. Despite robust evidence supporting dietary intervention, fewer than 15% of patients receive nutrition counseling during internal medicine consultations.Objective: To synthesize current evidence regarding the efficacy of nutrition in chronic disease management and to identify actionable strategies for integrating dietary counseling into clinical practice.Methods: This narrative review evaluated literature published between 2000 and 2025 across Web of Science, PubMed, Google Scholar, and Scopus. Analysis focused on systemic barriers, implementation frameworks, and the clinical impact of nutrition on chronic illness. Preference was given to randomized controlled trials (RCTs), clinical practice guidelines, and meta-analyses.Results: Evidence suggests that the Mediterranean, DASH, plant-based, and Portfolio diets achieve improvements in blood pressure, glycemic control, and cardiovascular risk reduction comparable to pharmacological interventions. However, integration is hindered by insufficient nutritional education in medical training, time constraints during clinical encounters, fragmented electronic health record (EHR) interoperability, and misaligned reimbursement models. Emerging solutions include multidisciplinary team-based care involving registered dietitians, standardized screening protocols, telehealth innovations, and AI-driven clinical decision support systems.Conclusion: Nutrition remains a significantly underutilized therapeutic modality in internal medicine. To establish nutrition as a fundamental tool of care, systemic reforms in medical education, reimbursement structures, and digital health integration are essential. Transitioning toward value-based care and personalized nutrition has the potential to revolutionize chronic disease management and improve long-term patient outcomes.